Only Rape! Human Rights and Gender Equality for Refugee Women From Refugee Camps to the United Nations - Pittaway, Eileen; Bartolomei, Linda Albina (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book charts the roller coaster ride taken by the authors over the past 33 years, in the ongoing fight to acknowledge, prevent, and respond to the rape and sexual abuse of women in conflict and displacement situations. They have worked with an international network of academics, refugee women, and human rights activists in 22 countries. The story moves between refugee camps and the United Nations, refugee settlements in cities and national governments. Theory and ethical research methods are an important part of the story. At times it is very confronting, sometimes amusing and often uplifting. Eileen Pittaway, adjunct associate professor was director of the Centre for Refugee Research, UNSW for 14 years. The major focus of her work is the prevention of and response to the rape, sexual abuse, and gender-based violence experienced by refugee women, and the fight for their voices to be included in solutions. In 2012, she was made a Member of the Order of Australia for her work with refugees. Linda Albina Bartolomei is a co-convenor of the UNSW Forced Migration Research Network (FMRN). For over 20 years she has been engaged in action research projects exploring the challenges faced by refugee women and girls at risk in camps and urban settings. She is currently co-leading a multi-year project in four countries in the Asia- Pacific to support the implementation and monitoring of the commitments to refugee women and girls in the Global Compact on Refugees. .
Chapter 1 - Prologue -- Chapter 2 - Opening Pandora's Box: Rape, Sexual Abuse and refugee women - 1989 - 1990 -- Chapter 3 - From the Local to the International: Domestic Politics and International Advocacy - 1990 - 1992 -- Chapter 4 - Rape as a War Crime: The Road to the 4TH world Conference, Beijing - 1993 -1995 -- Chapter 5 - Interlogue -- Chapter 6 - Beijing the Never-Ending Story of Rape and Sexual Torture - 1996 - 2000 -- Chapter 7 - Intersectionality, Identity and Refugee Women-2001 - 2002 -- Chapter 8 - Refugee Women at Risk and Reciprocal Research 'Stop Stealing Our Stories': Beyond do no Harm - 2003 - 2004 -- Chapter 9 - The Power of Women Speaking Out: A Risk Assessment and Response Tool, a CSW Resolution and a UNCHR Conclusion -2005 -2008 -- Chapter 10 - Survivors, Protectors, Providers: Refugee Women Speak Out From Gender Mainstreaming to the Regional Dialogues - 2009 -2011 -- Chapter 11 - Anger and Despair - Naming the 'Elephants in the Room' - 2012 -2016 -- Chapter 12 - Refugee Women From the Margins to the Centre -2017 - 2020 -- Chapter 13, Epilogue -The Move from Rhetoric to Reality - 2021 - 2022.
Keywords: Human rights; Biotechnology; Feminism; Feminist theory; Human Rights; Biotechnology; Feminism and Feminist Theory